Taxonomia e aspectos paleoecológicos dos ostracodes do Maastrichtiano – Daniano (formações Jagüel e Roca) da seção de Cerro Azul, General Roca, Bacia De Neuquén, Argentina. - Ceolin, Daiane (Universidade do Vale do Rio dos Sinos, 2015)
The Neuquén basin is known by its rich and well preserved fossil content exposed in a complete and excellent sedimentological records, constituting an ideal location for study of the K–Pg boundary. Despite of the large number of published works in the area, recently new sections have been discovered. Among these, the Cerro Azul section is of great importance due to its abundant and well preserved ostracod fauna which spans the K–Pg boundary. In the present study, a total of 27 samples from the Jagüel and Roca formations (Maastrichtian-Danian) of the Nequén basin were analysed. The faunal study allowed the recognition of 113 species, belonging to 51 genera and 11 families. From these, 10 new genera, 41 new species and a new subfamily Nodoconchiinae, were described. The new species are: Cytherella saraballentae, Cytherella semicatillus, Paracypris bertelsae, Paracypris imaguncula, Argilloecia abnormalis, Argilloecia concludus, Argilloecia hydrodynamicus, Bythoceratina cheleutos, Phelocyprideis acardomesido (new genus and species), Eucythere dinetos, Krithe crepidus, Cytheropteron hyperdictyon, Cytheropteron bidentinos, Cytheropteron translimitares, Aversovalva glochinos, Eucytherura stibaros, Hemingwayella verrucosus, Heinia prostratopleuricos, Loxoconcha (s.l.) posterocosta, Keijia circulodictyon, Keijia kratistos, Paramunseyella epaphroditus, Munseyella costaevermiculatus, Ameghinocythere archaios, Aleisocythereis polikothonus, Castillocythereis multicastrum (new genus and species), Castillocythereis albertoriccardii, Cythereis stratios, Cythereis clibanarius, Cythereis trajectiones, Henryhowella (Wichmannella) praealtus, Hysterocythereis paredros (new genus and species), Hysterocythereis coinotes, Hysterocythereis diversotuberculatus, Orthrocosta decores (new genus and species), Orthrocosta atopos, Orthrocosta phantasia, Sthenarocythereis erymnos (new genus and species), Nodoconcha polytorosa, Nodoconcha sanniosis, Nodoconcha upsilon and Ectonodoconcha lepidotus (new genus and species). The new genera Aleisocythereis, Apatoleberis, Apobradleya and Petalocythereis were proposed to accomodate species previously described for Neuquén Basin. Some evolutionary aspects of the identified fauna, mainly regarding the Trachyleberidinae and Nodoconchiinae subfamilies, are discussed. The paleoecological interpretation based on the faunal association present in the Cerro Azul section allows the inference of a marine, inner to mid-shelf environment, with a dominance of the family Trachyleberididae in both Maastrichtian and Danian rocks. The K–Pg boundary is marked by a considerable faunal change, characterized by the appearance of a richer and more abundant Danian fauna alongside 21 species which survived the extinction event. The presence of predation on the carapaces is documented, possibly caused by naticid snails.
Keywords: Bacia de Neuquén; Ostracode; Cretáceo - Paleógeno; Formação Jagüel; Formação Roca; Argentina; Neuquén Basin; Ostracod; Cretaceous - Paleogene; Jagüel Formation; Roca Formation; ACCNPQ::Ciências Exatas e da Terra::Geologia